SELF-DETERMINATION AND NATIONALISM IN THE BORDER RE-ARRANGEMENTS IN THE HORN OF AFRICA - Behr, Agnes Wanjiru (American Journal of International Relations, 2018)
Purpose: The study sought to understand self-determination and the challenges posed to the borders in the Horn of Africa through a precise analysis of the notion and its application in the Horn of Africa. Methodology: The research used qualitative methodology via primary and secondary data. Primary data engaged historiography through archival materials, documents and field interviews while secondary data was from published journals and books. The study also used magazines, newspapers and internet materials, and films to synthesize the data for validation of the outcome. Result: Self-determination affects state borders and therefore confirms that borders are arbitrary constant formations. Borders include social-cultural norms which entail ethnic identities and state norms. The latter involves inviolability of borders, fixed territory, exclusive citizenship rights and sovereign rights. Therefore, challenges of the state borders in the Horn appears as a clash between the social-cultural norms and state norms. Whereas the first calls for accommodation and negotiated legal spaces, the latter retains a rigid notion of borders which resists a shift of the same. However, successful self-determination referendum by a group within a state followed by consent of the state and recognition by the United Nation (UN) legitimizes international border shifts through the formation of new unique states. A unique contribution to theory, practice, and policy: Self-determination is concomitant with border constructions. Therefore a need in the understanding that natural borders do not exist. States should appreciate a shift in any border as an attempt to self-govern where the hosting regime fails to uphold the same. Self-determination implies retaining a cultural identity and a norm unique from the existing states where annihilation threat towards a group is present. States should not necessarily interpret self-determination as a danger but a mode of negotiation as engrained in pre-colonial African borders. Furthermore, self-determination does not encourage the use of force against other states but promotes the idea of negotiated spaces through plebiscites the acceptance of which results in redrawn borders and the opposite retains status quo.